2018
DOI: 10.1039/c7ob02928d
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble hydrophobic peptoids via a minor backbone modification

Abstract: Peptoids - oligomers of N-substituted glycine - are an important class of peptide mimics that are widely used in areas ranging from biology and medicine to metal binding and catalysis. The utility of peptoids, however, especially for applications in aqueous solutions, is often hampered by the hydrophobic nature of their sequences dictated by structural and functional requirements. Herein we describe a simple method to solubilize hydrophobic peptoids in water without modifying their original sequences, via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Interestingly, we have recently shown that the incorporation of one or more piperazine units within the backbone of hydrophobic peptoids ensures their water-solubility, while maintaining their sequence and structure. [27] Capitalizing on these findings, we present here a new, water-soluble and helical peptoid chelator, which is selective for Cu 2+ , and describe how we applied it for the removal of Cu 2+ from Ab peptides, in aqueous medium, in order to stop the formation of ROS associated with AD, including in presence of Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we have recently shown that the incorporation of one or more piperazine units within the backbone of hydrophobic peptoids ensures their water-solubility, while maintaining their sequence and structure. [27] Capitalizing on these findings, we present here a new, water-soluble and helical peptoid chelator, which is selective for Cu 2+ , and describe how we applied it for the removal of Cu 2+ from Ab peptides, in aqueous medium, in order to stop the formation of ROS associated with AD, including in presence of Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, P1 is hydrophobic and water insoluble, properties that limit its utilization as a drug candidate, despite its selectivity to Cu 2+ . Interestingly, we have recently shown that the incorporation of one or more piperazine units within the backbone of hydrophobic peptoids ensures their water‐solubility, while maintaining their sequence and structure [27] . Capitalizing on these findings, we present here a new, water‐soluble and helical peptoid chelator, which is selective for Cu 2+ , and describe how we applied it for the removal of Cu 2+ from Aβ peptides, in aqueous medium, in order to stop the formation of ROS associated with AD, including in presence of Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we observed a positive effect on solubility as well as a retained folding propensity when incorporating a piperazine-containing N-terminal capping group, 55 as originally reported by Maayan and co-workers. 75 We therefore decided to add this feature to all oligomer designs in the current study. It was also decided to apply the previously developed synthetic strategy based on trimer segment couplings.…”
Section: Resultsmentioning
confidence: 99%